The unity of mystical traditions : the transformation of consciousness in Tibetan and German mysticism - Studstill, Randall (Studies in the history of religions ;, 2005)
The book supports an ecumenical theory of mysticism through a comparative analysis of Tibetan Dzogchen and German mysticism. Using a systems model of consciousness as an interpretive framework, it shows how the distinct doctrines and practices of these two traditions function in parallal, equally transformative ways.